Browning, Victorian poetics and the romantic legacy : challenging the personal voice - Martens, Britta, 1973- (Ashgate, 2011)
Taking an original approach to Robert Browning's poetics, Martens analyses his work in relation to Romanticism and an evolving Victorian poetic culture. She goes beyond reductive interpretations of Browning as a self-effacing poet to reveal a highly self-conscious, self-dramatising and conflicted engagement with the Romantic tradition. Martens' Browning is a poet of complex contradictions and an illuminating case study in voice, authorial authority and self-reference.